Metaphorical Perceptions of Pre-Service Mathematics Teacher towards Art in Mathematics Activities - Kükey, Ebru; Kükey, Hilal; Tutak, Tayfun (My University, 2019)
The aim of the study is to determine the art perceptions of inmathematics activities of pre-service mathematics teachers throughmetaphors. The method of the study is designed as a case study ofqualitative research designs. The study group consisted of 92 preservice teachers studying in mathematics teaching program. The datawere collected with a form where pre-service teachers completed thestatement “Mathematics activities are like the art of<, because<”.Content analysis was used to analyze the answers of pre-serviceteachers. As a result of the evaluations, the metaphorical perceptions ofpre-service mathematics teachers towards art were determined under 5themes. These themes are expressed as mind, profession, mathematical, lifeand activity. As a result of the evaluations, the metaphorical perceptionsof pre-service teachers about art in mathematics activities weredetermined.
Keywords: Eğitim; Eğitim Araştırmaları; Matematik; Sanat